The Role of the interstice staminodes of Bucephalandra Schott (Araceae : Schismatoglottideae) - Wong Sin, Yeng; Boyce, P.C (International Aroid Society ,Inc., 2013)
Fieldwork in various parts of Borneo has now conclusively shown that the motile staminodes of the Bucephalandra Schott are not part of the pollination mechanics but, rather, are implicated in post-anthesis and pre-dispersal protection of the developing fruits.